1999
DOI: 10.1046/j.1442-2050.1999.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal motor disturbances in progressive systemic sclerosis*

Abstract: Ten patients with progressive systemic sclerosis (PSS) and esophageal symptoms (group 1) and 10 control subjects were studied. Esophageal electromanometry using the intermittent pull-through technique and catheter perfusion with distilled water were performed in all patients and individuals. The variables studied were pressure amplitude in the lower esophageal sphincter (LES) (mmHg) and deglutition wave amplitude (mmHg at 5, 10 and 15 cm above LES). In PSS patients, the average LES pressure was 18.5 +/- 4.6 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…9,10 Our study, however, shows that peristalsis is preserved in all patients with CTD when no other organs other than the esophagus are involved. Specifically, we demonstrated that in most patients with cutaneous and gastrointestinal manifestations only, the motility profile was similar to that of patients with GERD but without CTD.…”
Section: Connective Tissue Disorders and Esophageal Motilitymentioning
confidence: 60%
“…9,10 Our study, however, shows that peristalsis is preserved in all patients with CTD when no other organs other than the esophagus are involved. Specifically, we demonstrated that in most patients with cutaneous and gastrointestinal manifestations only, the motility profile was similar to that of patients with GERD but without CTD.…”
Section: Connective Tissue Disorders and Esophageal Motilitymentioning
confidence: 60%
“…Although the picture appears myogenic, it follows a course with degeneration in Auerbach's plexus. Esophageal emptying is delayed due to ineffective peristaltic movements; lower esophageal sphincter pressure falls and gastroesophageal reflux develops [7]. Related to this, candida esophagitis, erosive esophagitis, Barrett's esophagus, diverticles, fibrous stricture, and malignancy may develop as complications.…”
Section: Discussionmentioning
confidence: 99%
“…Stricture and findings compatible with esophagitis may be determined in endoscopic examination. Manometrically, low-amplitude peristaltic contractions and a reduction in lower sphincter pressure are typical [6, 7]. Pyrosis, dysphagia, acid regurgitation, aspiration, chest pain, nausea, and vomiting are complications frequently encountered with esophageal involvement of scleroderma.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal manometry was performed using the usual technique of our laboratory (7) which included an 8-channel probe, physiographic process and continuous infusion device. Through the analysis of the graphic records the following parameters were evaluated: lower and upper sphincter resting pressure of the esophagus (LES, UES) and its peristalsis.…”
Section: • Esophageal Manometrymentioning
confidence: 99%